Steroids from Atactodea striata and Their Cytotoxic Activity against MCF-7 Breast Cancer Cell Lines - Evan Hadrian; Aprilia Permata Sari; Tri Mayanti; Desi Harneti; Rani Maharani; Darwati Darwati; Kindi Farabi; Celcius Waranmaselembun; Supriatno Salam; Sofa Fajriah; Muhamad Nurul Azmi; Unang Supratman (Universitas Gadjah Mada, 2023)
Marine environment is known as a source of potential steroids with multiple biological activities, one of which is an anticancer agent. Atactodea striata are one of the seashells distributed in Indonesia located in the Kei Islands, Southeast Maluku. During the course of our continuing search for biologically active substances from Indonesia seashells, seven steroids have been isolated from the n-hexane fraction of A. striata and they were identified as 7β-hydroxy-sitosterol (1), campesterol (2), β-sitosterol (3), cholesterol (4), 5α,8α-epidioxycholest-6-en-3-β-ol (5), 7-keto-cholesterol (6), and 7α-hydroxy-cholesterol (7). The structure was identified by spectroscopic methods including 2D NMR techniques, FTIR, HRTOFMS, and chemical shift comparison with previously reported spectral data. Compounds 1-7 were evaluated for their cytotoxic effects against MCF-7 breast cancer cells and showed weak or no anticancer activity.